HIV and carotid atherosclerosis: a mediational model. Issue 7 (2nd July 2020) - Alcaide, Maria Luisa; Rodriguez, Violeta J.; Abbamonte, John M.; Pallikuth, Suresh; Langlie, Jake; Soni, Manasi; Weiss, Stephen M.; Hurwitz, Barry E.; Pahwa, Savita; Jones, Deborah L.; Kumar, Mahendra
ABSTRACT: Cardiovascular disease (CVD) is the leading cause of death in the US and is a significant contributor to morbidity and mortality for people living with HIV (PLWH). This study examined the association between HIV infection, cocaine usage, and inflammatory markers, and their combined association with carotid atherosclerosis among young and middle-aged adults with HIV. Participants ( N = 494) were enrolled based on HIV status and cocaine use. Blood pressure, body mass index (BMI), and cocaine use were assessed. Cytokines and growth factors, IL-1a, IL-6, TNFα and VEGF, and immune activation markers, sCD14 and sCD163 were measured. Participant age was 36.2 years (SD = 9.5); 50% were male, 49% female and 1% transgender; 39% were HIV-positive, 50% were current or past smokers, and 39% endorsed cocaine use. A path analysis showed an indirect effect of HIV serostatus on the presence of carotid atherosclerotic plaques ( Indirect Effect = 0.048, SE = 0.024, p = .043), when controlling age, BMI, smoking, and cocaine use. This effect was mediated by inflammatory markers and changes in blood pressure. Findings point to putative underlying mechanisms leading to atherosclerosis among PLWH.